A STUDY ON THE EFFECT OF SCHOOL LEADERSHIP AND TEACHERS’ PERFORMANCE ON STUDENTS’ SATISFACTION - Sukris Sutiyatno, Sugeng Wahyudiono (TRANSFORMASI, 2020)
This research aimed to reveal the effect of school leadership on teachers’ performance and its impact on the students' achievement of private vocational high school. This study made use of a quantitative approach with survey method. The population of this study was second-year students and teachers of private VHS. The instrument of data collection used questionnaires. The data were analysed by means of path analysis. This study found that school leaders gave a positive effect on the students’ satisfaction directly and indirectly through the mediation of teachers’ performance. A school leadership gave a positive effect on the teachers’ performance and teachers’ performance also gave a positive effect on the students’ satisfaction. The implication of this research is VHS should empower the role of school leadership to improve teachers’ performance to meet the students’satisfaction and expectation. Keywords: school leadership, teachers’ performance and students’ satisfaction